Euphorbia erythroclada Boiss. - a Little Known Species from Maharashtra - Billore, K. V. (Indian Forester, 1969)
The note provides an interesting record of the species, Euphorbia erythoclada Boiss. collected after over 100 years from Thana District, Maharashtra State; a detailed description with illustration is appended.